Molecular Mechanisms of Resistance to Ceftazidime/Avibactam in Clinical Isolates of Enterobacterales and Pseudomonas aeruginosa in Latin American Hospitals - Mojica, María Fernanda (2023)
Ceftazidime-avibactam (CZA) is the combination of a third-generation cephalosporin and a new non-b-lactam b-lactamase inhibitor capable of inactivating class A, C, and some D b-lactamases. From a collection of 2,727 clinical isolates of Enterobacterales (n = 2,235) and P. aeruginosa (n = 492) that were collected between 2016 and 2017 from five Latin American countries, we investigated the molecular resistance mechanisms to CZA of 127 (18/2,235 [0.8%] Enterobacterales and 109/492 [22.1%] P. aeruginosa). First, by qPCR for the presence of genes encoding KPC, NDM, VIM, IMP, OXA-48-like, and SPM-1 carbapenemases, and second, by whole-genome sequencing (WGS). From the CZA-resistant isolates, MBL-encoding genes were detected in all 18 Enterobacterales and 42/109 P. aeruginosa isolates, explaining their resistant phenotype. Resistant isolates that yielded a negative qPCR result for any of the MBL encoding genes were subjected to WGS. The WGS analysis of the 67 remaining P. aeruginosa isolates showed mutations in genes previously associated with reduced susceptibility to CZA, such as those involved in the MexAB-OprM efflux pump and AmpC (PDC) hyperproduction, PoxB (blaOXA-50-like), FtsI (PBP3), DacB (PBP4), and OprD. The results presented here offer a snapshot of the molecular epidemiological landscape for CZA resistance before the introduction of this antibiotic into the Latin American market. Therefore, these results serve as a valuable comparison tool to trace the evolution of the resistance to CZA in this carbapenemase-endemic geographical region.